2022
DOI: 10.1155/2022/1850305
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linoleic Acid Treatment Attenuates Cancerous features in Hepatocellular Carcinoma Cells

Abstract: Background. A growing number of hepatocellular carcinoma (HCC), and recurrence frequency recently have drawn researchers’ attention to alternative approaches. The concept of differentiation therapies (DT) relies on inducing differentiation in HCC cells in order to inhibit recurrence and metastasis. Hepatocyte nuclear factor 4 alpha (HNF4α) is the key hepatogenesis transcription factor and its upregulation may decrease the invasiveness of cancerous cells by suppressing epithelial-mesenchymal transition (EMT). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…62 Moreover, Miri-Lavasani et al reported that the treatment of HCC cells using conjugated linoleic acid, as a natural ligand of HNF4α, decreased EMT marker level, migration, and proliferation capacities. 63 Taken together, this study provided a comprehensive and integrated insight into the importance of HNF4α protein in linking several key modules involved in HCC and proposed it as a potential therapeutic target. We revealed that overexpression of HNF4α protein by a synthetic AS lncRNA in the physiological range could simultaneously modulate aberrant changes in metabolism and cellular behavior.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…62 Moreover, Miri-Lavasani et al reported that the treatment of HCC cells using conjugated linoleic acid, as a natural ligand of HNF4α, decreased EMT marker level, migration, and proliferation capacities. 63 Taken together, this study provided a comprehensive and integrated insight into the importance of HNF4α protein in linking several key modules involved in HCC and proposed it as a potential therapeutic target. We revealed that overexpression of HNF4α protein by a synthetic AS lncRNA in the physiological range could simultaneously modulate aberrant changes in metabolism and cellular behavior.…”
Section: Discussionmentioning
confidence: 69%
“…HNF4α is a tumor suppressor factor, Cheng et al demonstrated that the combination of HNF1A , HNF4A , and FOXA3 synergistically reprograms HCC cells to hepatocyte‐like cells, in which the malignant phenotype is reduced, and hepatocyte‐specific characteristics retrieved 62 . Moreover, Miri‐Lavasani et al reported that the treatment of HCC cells using conjugated linoleic acid, as a natural ligand of HNF4α, decreased EMT marker level, migration, and proliferation capacities 63 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation